Case report: Safety and efficacy of synergistic treatment using selinexor and azacitidine in patients with atypical chronic myeloid leukemia with resistance to decitabine - Liu, Lu; Song, Xiaofeng; Dong, Wenhao; Li, Zhao; Guo, Dongmei (Frontiers in Oncology, 2024)
Background Atypical chronic myeloid leukemia (aCML) is a BCR::ABL1 negative myelodysplastic/myeloproliferative neoplasm with poor overall survival. Some patients can be treated by allogeneic hematopoietic stem cell transplantation (allo-HSCT) from suitable donors. The effectiveness of decitabine or azacitidine (AZA) has recently been reported; however, their combined efficacy with selinexor has not yet been reported. Case description In this study, we report the case of a patient with aCML who was successfully treated with selinexor combined with AZA. A 67-year-old man with a history of gastric mucosa-associated lymphoid tissue (MALT) lymphoma was admitted to the hospital with fatigue and emaciation. He was diagnosed with aCML and no longer responded to decitabine treatment after undergoing seven cycles. The patient was subsequently administered hydroxyurea (HU), selinexor, and AZA. After four courses of combination therapy, his blood cell counts improved; he no longer required transfusions and was able to discontinue HU. The patient continued receiving selinexor and AZA without severe complications. This case is the first to show that combinatorial selinexor and AZA therapy can effectively treat aCML. Conclusion Our case sheds light on the importance of selinexor and AZA combined therapy in the exploration of new treatment strategies for aCML. Moreover, this treatment approach offers the possibility of bridging with allo-HSCT.